Analysis of the Gap Between University and Software Industry in Argentina: A Teaching Perspective and Potential Solutions - López-Nocera, Marcelo (2024)
This study examines the gap between universities and companies. It specifically aims to identify relevant cognitive variables according to institutional theory (such as motivations, beliefs, concepts, and perceptions) for the agents studied (in this case, university professors) and quantify these variables. The research focuses on the National Technological University and the programs related to the software industry to explore ways to reduce the gap and improve the relationship between the two sectors.